2021
DOI: 10.2196/27298
|View full text |Cite
|
Sign up to set email alerts
|

Brain Mechanisms of Virtual Reality Breathing Versus Traditional Mindful Breathing in Pain Modulation: Observational Functional Near-infrared Spectroscopy Study

Abstract: Background Pain is a complex experience that involves sensory-discriminative and cognitive-emotional neuronal processes. It has long been known across cultures that pain can be relieved by mindful breathing (MB). There is a common assumption that MB exerts its analgesic effect through interoception. Interoception refers to consciously refocusing the mind’s attention to the physical sensation of internal organ function. Objective In this study, we dissec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Corticotropin-releasing factor neurons of the mPFC project directly to the nucleus accumbens and increased activity in these neurons in the setting of NeuP facilitates behavioral responses to morphine reward ( 63 ). Interestingly, the practice of traditional mindful breathing was found to successfully modulate functional connectivity between the prefrontal and primary somatosensory cortices and relieve pain ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Corticotropin-releasing factor neurons of the mPFC project directly to the nucleus accumbens and increased activity in these neurons in the setting of NeuP facilitates behavioral responses to morphine reward ( 63 ). Interestingly, the practice of traditional mindful breathing was found to successfully modulate functional connectivity between the prefrontal and primary somatosensory cortices and relieve pain ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, different types of breathing training such as virtual reality breathing and traditional mindful breathing also appear to improve pain thresholds. Interestingly, stimulation of different brain regions has been reported which varies depending on the breathing training method [ 48 ]. This suggests that breathing may have also independently affected pain regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study demonstrated a virtual reality breathing (VRB) protocol with virtual 3D-lungs that synchronized with the participants’ breathing cycles in real time, providing the participant with an immersive visual-auditory experience. When exposed to the VRB, the subjects decreased their pain sensitivity in the same manner as the participants using traditional meditative breathing but with opposing brain mechanisms for analgesia (Hu et al 2021). The rising visual-auditory sensations brought by the immersive VR experience cut off the connection between the competing pain inputs and a selective mind–body disconnection.…”
Section: Digital Dentistry For Diagnosis and Treatmentmentioning
confidence: 99%